High Frequency Characterization of Thin-Film Redistribution Layers for Embedded Wafer Level BGA - Wojnowski, Maciej; Engl, Mario; Brunnbauer, M.; Pressel, Klaus; Sommer, Grit; Weigel, Robert (9th Electronics Packaging Technology Conference, 2007)
We present high frequency characterization of thin-film redistribution layers for an embedded wafer level BGA package technology. This technology is based on a "molded reconfigured wafer" concept where the chip area is not the limitation for external contacts. The flexible thin-film redistribution layers in the fan-out area enable the realization of high-density, low-loss transmission lines with precisely controlled characteristic impedance. Due to low-loss dielectrics and thick copper metallization, we can realize high-Q passives. We show measurement results of coplanar transmission lines with insertion loss 0.2 dB/mm at 60 GHz. We present measurement results of high-Q inductors with inductance values ranging from 2.8 nH to 30 nH and a quality factor of up to 39. The results demonstrate an outstanding potential of the embedded wafer level BGA concept for high frequency SiP applications.
elib2cris::1512001600,wojnowski2007
Keywords: ball grid arrays; coplanar transmission lines; dielectric materials; thin films; Copper; thick copper metallization; frequency 60 GHz; Impedance